Management of radiation-induced tracheocutaneous tissue defects by transplantation of an ear cartilage graft and deltopectoral flap - Riedel, Frank; Gößler, Ulrich; Grupp, Stephan; Bran, Gregor M.; Hörmann, Karl; Verse, Thomas (Auris, nasus, larynx, 2006)
Patients suffering from head and neck cancer often require temporary tracheostomy during therapy. The tracheostomy can usually be closed when postoperative swelling decreases and swallowing ability recovers. However, some patients, especially after adjuvant radiotherapy, may develop severe chronic wounds resulting in persistent tracheocutaneous fistula. Local wound care and plastic reconstruction strategies are required in such cases. We present two patients with head and neck cancer treated with primary surgical regimen including temporary tracheostomy and adjuvant radiotherapy. Both patients developed a persistent, poorly healing wound with persistent tracheocutaneous tissue defect. After local debridement and wound care, the peristomal necrotic tissue was excised down to the level of the trachea. The defect of the anterior tracheal wall was closed with a autogenous ear cartilage graft. The graft was harvested from the cavum conchae and sutured to the tracheal defect. The soft tissue defect was covered by transposition of a well-vascularized, fasciocutaneous deltopectoral flap. In both cases, the flaps healed satisfactorily. The donor defect was closed primarily. Complications were not observed in these two cases. A flexible tracheo-bronchoscopy showed no stenosis of the trachea at the site of cartilage graft transplantation. In conclusion, treatment of persistent radiated tracheocutaneous defects by cartilage graft and deltopectoral flap turned out to be a safe and reliable procedure which can be performed as a one-stage method with low morbidity at the donor site.